Effectiveness of Lysol and Glutaraldehyde 2 % in high-speed handpieces after being subjected to mechanical cleaning - Lozano Torres, Ana Rocío (2019)
Chemical disinfection is an important procedure used in the dental field that aims to prevent the spread of pathogenic microorganisms that may affect health. Objective: To determine the disinfectant effectiveness of the Lysol and Glutaraldehyde 2% agent in aerosol in high-speed handpieces in ninth semester students who attend the Integral Clinic of the School of Dentistry of the Central University of Ecuador (FO-UCE) period 2017. Materials and methods: In vitro experimental study. The sample was obtained from 40 high-speed handpieces before and after subjecting the turbines to a disinfection process using two agents applied in aerosolized Lysol and Glutaraldehyde 2%. The samples were taken from two sites, head and handle. The samples were then transported to the FO-UCE Microbiology laboratory in tubes with thioglycolate, subsequently seeded in the blood agar medium and incubated for 48 hours at 37 ° to finally observe the formation of colony forming units. The statistical analyzes of ANOVA and Tukey with a significance level of 5% were used. Results: An effect on the bacterial reduction of 0.6 CFU glutaraldehyde and 1.3 CFU lysol was observed after use. Both glutaraldehyde and lysol showed significant differences before and after use (p <0.001), with no differences between the two after mechanical disinfection with both aerosol substances (p = 1.0). Conclusion: Glutaraldehyde and Lysol aerosol were effective in disinfecting high speed handpieces.